A rare case of type 1 citrullinemia in newborn - Rathore, Ashutosh Singh; L., Guntupalli Shravya; Seth, Dhrumika (International Journal of Contemporary Pediatrics, 2022)
Citrullinemia type I (CTLN1) is a rare and lethal autosomal recessive genetic disorder. CTLN1 is caused by deficiency or absence of the enzyme arginino succinate synthetase (ASS). We reported a rare case of CTLN1 in a male full-term neonate. This report related to a full-term male child, born out of 3rd degree consanguineous marriage, admitted at our unit on DOL-3 with severe dehydration. ABG showed persistent severe metabolic acidosis despite of adequate treatment. So, suspecting an inborn error of metabolism (IEM) investigations were done in which we found high serum ammonia, serum lactate and urinary sodium. TMS and GCMS were done which observed a profile which can be seen in case of citrullinemia. CTLN1 is a rare and lethal genetic disorder. High index of suspicion is needed when patients present with such complex symptoms. Diagnosing and timely intervention helps in reducing the morbidity and mortality and with treatment, people with citrullinemia type 1 can have normal growth and development.